Similarity solution for undrained cylindrical cavity contraction in anisotropic modified Cam-clay model soils. (April 2020) - Zhang, Junran; Li, Lin; Sun, De'an
Abstract: This paper develops a similarity solution for undrained cylindrical cavity contraction in anisotropic modified Cam-clay (AMCC) model soil. An AMCC model incorporating the spatially mobilized plane (SMP) criterion is used to model the behaviors of soil during cavity contraction. Based on the equilibrium equation, constitutive equation, consistency equation, continuity equation and the undrained condition, the problem is reduced to solving a system of first-order ordinary differential equations. The proposed solution is validated by a FLAC 3D numerical model and compared with the solution that does not incorporate SMP criterion to demonstrate the effects of three-dimensional strength on the cavity contraction responses.